2014
DOI: 10.1038/oncsis.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the pentose phosphate pathway by an androgen receptor–mTOR-mediated mechanism and its role in prostate cancer cell growth

Abstract: Cancer cells display an increased demand for glucose. Therefore, identifying the specific aspects of glucose metabolism that are involved in the pathogenesis of cancer may uncover novel therapeutic nodes. Recently, there has been a renewed interest in the role of the pentose phosphate pathway in cancer. This metabolic pathway is advantageous for rapidly growing cells because it provides nucleotide precursors and helps regenerate the reducing agent NADPH, which can contribute to reactive oxygen species (ROS) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(127 citation statements)
references
References 67 publications
8
116
2
1
Order By: Relevance
“…Interestingly, it was shown in vitro and in xenograft models that prostate cancer cell lines are highly dependent on the phosphofructokinase-fructose-bisphosphatase 2 isoform PFKFB4 and on glucose-6-phosphate dehydrogenase [152,168]. Specifically, PFKFB4 drives the balance of glucose-6-phosphate and fructose-1,6-bisphosphate towards glucose-6-phosphate.…”
Section: Later Stage Prostate Cancer Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, it was shown in vitro and in xenograft models that prostate cancer cell lines are highly dependent on the phosphofructokinase-fructose-bisphosphatase 2 isoform PFKFB4 and on glucose-6-phosphate dehydrogenase [152,168]. Specifically, PFKFB4 drives the balance of glucose-6-phosphate and fructose-1,6-bisphosphate towards glucose-6-phosphate.…”
Section: Later Stage Prostate Cancer Metabolismmentioning
confidence: 99%
“…Latter is used as a substrate in the glucose-6-phosphate dehydrogenase reaction, the initial step of the oxidative pentose phosphate pathway. This suggests that a substantial portion of the glucose taken up is channeled through the pentose phosphate pathway for reduction of NADP + and consequently glutathione disulfide, as well as for de novo nucleotide biosynthesis [168,169]. Besides, prostate cancer still relies on oxidative phosphorylation, which is enforced by the interaction with cancer-associated fibroblasts as shown for PC-3 cells [127].…”
Section: Later Stage Prostate Cancer Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulated pathways related to metabolism would provide the necessity to cancer cells. At present, many study results have shown that these pathways were related to cancers, such as prostate cancer and breast cancer and so on (16,17). The current results showed that many metabolism pathways were significantly up-regulated in NSCLC, which mainly included purine metabolism (P value = 1.95e-44, ranked fourth), pyrimidine metabolism (P value = 1.01e-29, ranked fifth), glutathione metabolism (P value = 1.22e-27, ranked sixth), and amino sugar and nucleotide sugar metabolism (P value = 1.01e-21, ranked seventh).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the over expression G6PD was found to be required for prostate cancer cell proliferation [152] as its expression was increased upon androgen treatment in hormone sensitive prostate cancer cell lines. Thus it was suggested that G6PD activity could be used as a clinical marker for prostate cancer exams as its activity were found to be four times higher in carcinomas than in benign prostatic hyperplasia [152].…”
Section: In Disease Diagnosismentioning
confidence: 99%